Congenital Rubella Syndrome: An Overview of Clinical Presentations in Bangladeshi Children (Delta Medical College Journal, 2014)
Background: Congenital Rubella Syndrome (CRS) has long been characterized by the triad of deafness, cataract and cardiovascular malformations with or without mental retardation. Objective: This study was conducted to observe the clinical manifestations of CRS in children of Bangladesh. Materials and method: This cross sectional study was carried out in Dhaka Shishu (Children) Hospital, Dhaka, Bangladesh and National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh. Total 40 cases of CRS were enrolled from indoor and outpatient departments of these two hospitals, who were diagnosed according to standard case definition. Serological test for rubella antibody, chest X-ray, colour Doppler echocardiography, visual examination and hearing assessment were done in relative specialised centres. Results: The mean(±SD) age of the study subjects was 6.6(±5.7) months (range: 0-24 months). Among the subjects, 68% were male and 32% were female. Serum for rubella specific antibody revealed positive IgG in 60% cases and IgM in 28% cases. Neurological problem was the most frequently observed (90%) systemic complication followed by visual problem (83%), congenital hearing loss (80%) and congenital heart disease (78%). Cataract was the commonest (55%) among visual problems and microcephaly (62%) among neurological manifestations. Patent ductus arteriosus (PDA) was the most common (37.5%) isolated structural cardiac defect. Maximum (62.5%) children came from poor socioeconomic status. Maternal onset of infection was commonly detected in 1st trimester of pregnancy. Conclusion: Diagnosis of CRS and recognition of its versatile pattern of clinical presentation are crucial for better prognosis of the affected children. DOI: http://dx.doi.org/10.3329/dmcj.v2i2.20522 Delta Med Col J. Jul 2014; 2(2): 42-47